Gastro-oesophageal reflux disease in 20 dogs (2012 to 2014) - Muenster, M.; Hoerauf, A.; Vieth, M. (Journal of Small Animal Practice, 2017)
Objectives: To describe the clinical features of canine gastro-oesophageal reflux disease. Materials and Methods: A search of our medical records produced 20 dogs with clinical signs attributable to oesophageal disease, hyper-regeneratory oesophagopathy and no other oesophageal disorders. The clinical, endoscopic and histological findings of the dogs were analysed. Results: The 3-year incidence of gastro-oesophageal reflux disease was 0·9% of our referral dog population. Main clinical signs were regurgitation, discomfort or pain (each, 20/20 dogs) and ptyalism (18/20 dogs). Oesophagoscopy showed no (5/20 dogs) or minimal (13/20 dogs) mucosal lesions. In oesophageal mucosal biopsy specimens, there were hyperplastic changes of the basal cell layer (13/20 dogs), stromal papillae (14/20 dogs) and entire epithelium (9/20 dogs). Eleven dogs received omeprazole or pantoprazole and regurgitation and ptyalism improved in eight and pain diminished in six of these dogs within three to six weeks. Clinical Significance: Our findings suggest that canine gastro-oesophageal reflux disease is a more common clinical problem than hitherto suspected.
CRIS-Team Scopus Importer:2025-03-05